2023
DOI: 10.1186/s40104-022-00822-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological function of resveratrol and its application in animal production: a review

Abstract: With the prohibition of antibiotics in feed, plant functional substances have been widely studied as feed additives. Resveratrol, a natural stilbene, and a non-flavonoid polyphenol found in plants, possesses antioxidant, anti-inflammatory, and metabolic regulatory features. Resveratrol generated intense scientific and public interest, primarily due to its widely reported ability to prevent cancer, delay aging and alleviate related metabolic diseases. Recently, resveratrol has been studied and applied as a feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 165 publications
0
18
0
Order By: Relevance
“…Both compounds are urease inhibitors [ 41 ] and may reduce rumen ammonia production, resulting in a decrease in urea entering the blood. Resveratrol is a molecule with antioxidant properties that can exert the ability to either directly neutralize reactive oxygen species or indirectly upregulate the expression of cellular defensive pathways and genes [ 42 ]. A previous study showed that YSE increased the levels of blood GLU and TGs and reduced TC levels [ 43 ]; however, these effects were not noticed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds are urease inhibitors [ 41 ] and may reduce rumen ammonia production, resulting in a decrease in urea entering the blood. Resveratrol is a molecule with antioxidant properties that can exert the ability to either directly neutralize reactive oxygen species or indirectly upregulate the expression of cellular defensive pathways and genes [ 42 ]. A previous study showed that YSE increased the levels of blood GLU and TGs and reduced TC levels [ 43 ]; however, these effects were not noticed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system's reaction to pathogens like bacteria, viruses, and some harmful substances may also be modulated by RESV (Abedini et al., 2021 ). RESV has also been observed to decrease the survival of bacteria and decrease contagious pulmonary inflammation without observable host harm in vivo, resulting in attenuated diarrhea and inflammation in rotavirus‐infected piglets (Meng et al., 2023 ). Remarkably, it has been shown that RESV significantly increased immunological function in immunosuppressed animals, demonstrating a bidirectional regulatory influence on immunity (Song et al., 2022 ).…”
Section: Health Benefits Of Resvmentioning
confidence: 99%
“…Rich sources in phytochemicals and especially PCs have received great interest as feed supplements to attenuate or minimize the stress to which pigs are subjected during their productive cycle Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 12 May 2023 doi:10.20944/preprints202305.0933.v1 [22,23]. Its beneficial effect is attributed to the antioxidant potential per se of PCs and an improvement in mitochondrial function together with an increase in antioxidant enzyme activity [24,25]. In this context, under heat stress conditions and when the critical limit of the comfort zone is exceeded, animal's resort to certain mechanisms to minimize internal heat production and reach a homeostatic state [2].…”
Section: Physiological Variablesmentioning
confidence: 99%